The Acts of Drawing: ‘procedere’ and ‘cedere-pro’ (diségno, 2023)
ProcedereWanting to start with the meaning of the Italian verb ‘pro-cedere’ (to proceed) in the sense of going forth, of projecting, but above all of moving forward, I would like to turn to the figure of the Greek architect and sculptor Callimachus, the master par excellence of ‘leptótēs’ (‘grace,’ ‘subtlety,’ ‘refinement,’ ‘delicacy’), whom Marcus Vitruvius Pollio (80-15 B.C. ca.), in reference to the myth of the origin of the Corinthian order, indicates as the artist whom the Athenians, for the refinement and delicacy of his art of working in marble, called ‘chatatēxítechnos’ (who ruins art by exhausting it; perfectionist) [Vitruvio, IV.10, p. 373], a term composed of ‘katatēkō’ (‘consume,’ ‘destroy,’ ‘melt,’ ‘exhaust’) and ‘téchnē’ (‘art’), expressing the perfectionist tension of the artist, which leads to the exhaustion of art [Vitruvio, IV.10, p. 429]; Drawing, like the tension of Callimachus’ art, establishes a processuality, according to a syntagmatic and ordinal ritual, that exhausts the architectural design by proceeding toward one of its many possible solutions. [read more]